LASSO-type estimations for threshold autoregressive and heteroscedastic time series models. - Muhammad Jaffri Mohd Nasir (2020)
In this thesis, we propose Least Absolute Shrinkage and Selection Operator (LASSO) type estimators to perform simultaneous parameter estimation and model selection for five specific univariate and multivariate time series models, and develop several algorithms to compute these estimators.